1996
DOI: 10.1021/jp953744l
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity, NMR, Thermal Measurements, and Phase Diagram of the K2S2O7−KHSO4System

Abstract: The phase diagram of the catalytically important K2S2O7−KHSO4 solvent system has been investigated by means of electrochemical, thermal, and spectroscopic methods. The phase diagram exhibits a eutectic at ΧKHSO 4 = 0.94(1) with a temperature of fusion of 205 °C. No compound is formed in the system, but the strong α → β solid−solid transition of K2S2O7, found at 318 °C with ΔH tr = 21.8 kJ/mol, gives rise to a marked change in the slope of the liquidus curve at this temperature. The experimental phase diagram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
50
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 23 publications
4
50
0
Order By: Relevance
“…The melting temperature is 692 K and the enthalpy of melting is 21.2 kJ AE mol À1 . The measured melting temperatures in other studies are in agreement with Erikssen et al [16]: 673 K [14], 683 K [17], 692 K [18], 687 K [15], 687 K [11]. The enthalpy of melting is in good agreement with cryoscopic measurements by Hansen et al [18], who reported a value of 19.93 kJ AE mol À1 .…”
Section: Thermodynamic Data For Pure Compoundssupporting
confidence: 88%
See 4 more Smart Citations
“…The melting temperature is 692 K and the enthalpy of melting is 21.2 kJ AE mol À1 . The measured melting temperatures in other studies are in agreement with Erikssen et al [16]: 673 K [14], 683 K [17], 692 K [18], 687 K [15], 687 K [11]. The enthalpy of melting is in good agreement with cryoscopic measurements by Hansen et al [18], who reported a value of 19.93 kJ AE mol À1 .…”
Section: Thermodynamic Data For Pure Compoundssupporting
confidence: 88%
“…Others have also recorded a solid-solid transition at similar temperatures (603 K [17,19], 588 K [11,15]). Erikssen et al [16] and Meehan et al [17] have also recorded a transition at T = 473 K. No enthalpy data for this transition have been reported. Similarly as for Na 2 S 2 O 7 , the low-temperature solid-solid transition is very close to the eutectic temperature of (K 2 S 2 O 7 + KHSO 4 ), which is reported to be 478 K [16].…”
Section: Thermodynamic Data For Pure Compoundsmentioning
confidence: 99%
See 3 more Smart Citations